Effects of deglaciation on glaciovolcanism on Mars: Exploring the origin of tuyas in the Martian South Polar Region - Wiese, Joana (author) (2021)
It has been shown that glacially induced decompression rates under Vatnajökull cause an increase in mantle melt and enhancement in volcanic activity. Eruptions under ice can form tuyas, that can be used to constrain past ice sheet thickness. Several mountains in the Martian South Polar Region qualify as tuyas, but their exact origin is still unknown. In this study we reconstruct a palaeo ice sheet from the height and spatial distribution of these tuyas and study glacially induced decompression rates within the Martian mantle. In a finite element model we use the reconstructed ice sheet to constrain the surface pressure load and test different lithosphere thicknesses and linear deglaciation periods. We find a general decrease in decompression rates over depth and time. Results show that a decompression rate equal to the one induced by present-day deglaciation of Vatnajökull occurs at a lower depth inside the Martian mantle. Given that the mantle temperature is close to the solidus at this depth and magma ascent velocity is sufficiently high, mantle unloading due to ice melt could have contributed to the formation of the tuyas in the Martian South Polar Region. Our study proposes present-day deglaciation of Vatnajökull as a potential analogue for processes related to deglaciation on Mars. Aerospace Engineering